Cool zone with the Pain and the Great One - Blume, Judy.; Stevenson, James, 1929- (London : Macmillan, 2008)
More adventures at school and at home with Jake, a first-grader, and his older sister Abigail, known to each other as the Pain and the Great One.
Booklist.
New York Times.
School Library Journal.
Booklist, March 2008.
Horn Book, October 2008.
Kirkus Review, April 2008.
Keywords: Brothers and sisters -- Juvenile fiction; Families -- Juvenile fiction; Schools -- Juvenile fiction; Brothers and sisters -- Fiction; Family life -- Fiction; Schools -- Fiction; Family life -- Fiction; School stories; Siblings -- Fiction